Assessing Foreign-Language Students' Speaking Performance through a Digital Platform: Challenges and Findings - Ana Isabel Muñoz-Alcón; María Nieves Barahona-Esteban; Francisco Trullén-Galve (MDPI AG, 2023)
Online assessment of foreign-language learners, particularly of their oral skills, is a challenge for both students and teachers. Assessing language skills face to face, during a conversation between the examiner and the candidate, facilitates natural communication and is likely to provide a more accurate assessment of the student's language proficiency level. A change in the scenario and the use of digital tools can intimidate students and take away the naturalness and warmth of the interview. The purpose of this paper is to examine the suitability of Blackboard Collaborate as a learning management system for assessing English speaking skill and other factors that influence students' online performance. A total of 180 students from 7 different undergraduate programs in the fields of technology, environmental sciences and health sciences were assessed according to the structure of a standardized test. Using a mixed-methods approach, their results were contrasted with responses to a final survey to examine the positive or negative impact of online testing on students' attitudes, performance and achievement. The Blackboard digital platform proves to be a suitable and convenient online framework for optimal speaking performance, and the examiner's attitude is also a determining factor in students' success.